Asociación entre la analgesia epidural y el parto distócico en pacientes del Hospital General Regional No.1, Charo, Michoacán - Sánchez Sandoval, Yolima de Jesús (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
Neuraxial labor analgesia is a central nerve block technique that involves the injection of local anesthetic into the epidural or spinal space, thus blocking the pain impulses that are generated from the contraction of the uterus during labor. Birth. It is the safest and most effective technique, being the gold standard in pain management. Objective: To determine the association between obstetric analgesia and dystocic delivery in patients at Hospital General Regional No. 1 Charo, Michoacán. Methods: This study is observational, retrospective, cross-sectional and analytical. Records of 96 patients between 20 and 36 years of age with a term pregnancy of 37 to 40 weeks of gestation in the active phase of labor with care at the Hospital General Regional No. 1 Charo, Michoacán from January 1, 2022 to 30 will be included. June 2022. Results: Data from 96 patients were analyzed, divided into 2 groups with 48 patients each; with age in a range of 20 to 36 years, with a mean of 29.79 + 4.39 years, a mode of 34 years and a median of 30.5 years. A value of p= 0.02114 was obtained, being non-significant for the association of obstetric analgesia with dystocic delivery. Conclusion: The results obtained in this study disagree with those mentioned in the literature. Demonstrating the association 3.54 plus risk of dystocia with OA in our hospital, and that the presence of dystocia during labor is of multifactorial causes.

La analgesia neuroaxial del trabajo de parto es una técnica de bloqueo nervioso central, que implica la inyección de anestésico local en el espacio peridural o espinal, bloqueando así los impulsos dolorosos que se general a partir de la contracción del útero durante el trabajo de parto. Es el gold standard en el manejo del dolor. Objetivo: Determinar la asociación entre la analgesia obstétrica y el parto distócico en pacientes del Hospital General Regional No. 1 Charo, Michoacán. Métodos: Es un estudio observacional, retrospectivo, transversal y analítico. Se incluyeron expedientes de 96 pacientes entre 20 a 36 años con embarazo de término de 37 a 40 semanas de gestación en fase activa del trabajo de parto con atención en el Hospital General Regional No. 1 Charo, Michoacán desde el 1° enero 2022 al 30 junio del 2022. Resultados: Se incluyeron 96 pacientes, divididas en 2 grupos con 48 pacientes cada uno; con edad en un rango de 20 a 36 años, con una media de 29.79 + 4.39 años, una moda de 34 años y una mediana de 30.5 años. Se obtuvo un valor de p= 0.02114, siendo no significativo para la asociación de analgesia obstétrica con el parto distócico. Conclusión: Los resultados obtenidos discreparon con los mencionados en la literatura. Demostrando la asociación 3.54 más riesgo de distocias con AO en nuestro hospital, y que la presencia de distocia durante el trabajo de parto es de causas multifactoriales.
Facultad de Ciencias Médicas y Biológicas. Instituto Mexicano del Seguro Social. Especialidad en Anestesiología
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16391; info:eu-repo/classification/cti/3; FCMB-E-2023-0584; Analgesia obstétrica; Trabajo de parto; Parto distócico